Comparison Between Classic and Light Touch Massage on Psychological and Physical Functional Variables in Athletes: a Randomized Pilot Trial - Espí-López, PT, PhD, Gemma Victoria; Serra-Añó, PT, PhD, Pilar; Cuenca-Martínez , PT, MSc, Ferran; Suso-Martí, PT, MSc, Luis; Inglés, PT, PhD, Marta (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Despite the general belief of the benefits and the widespread use of massage in sport field, there are limited empirical data on possible effectiveness of massage on psychological and physical functional variables. Purpose: The main objective of the present study was to compare the effectiveness of classical and light touch massage on psychological and physical functional variables in athletes. Setting: Athletic club of Valencia Participants: 20 amateur athletes were recruited from two athletic clubs. Research Design: A single-blind, randomized, pilot-placebo trial. Intervention: The subjects were randomly allocated to two different groups: a) Massage group (MG) (n=10); b) Control group (CG) (n=10). The intervention period lasted one month (one session per week). Main Outcome Measures: Assessment of the participants was performed at baseline and 24 hours following the completion of the intervention. Outcome measures included hip flexion, knee extension, and mood state. Results: The results suggest that MG obtained better results on physical variables (p < .05). However, for both groups, trends suggest significant improvements in the overall mood state of the participants (p < .05). Conclusion: Our results suggest that classic massage could be an effective intervention to improve functional physical variables in athletes. However, trends suggest that a light touch intervention could provoke improvements in physiological measures.